Text to speech synthesis new paradigms and advances - Shrikanth Narayanan (IMSC Press multimedia series, 2005)
Bringing together research drawn from academic and industrial laboratories worldwide, this book covers areas including speech representations and modeling, data-driven synthesis schemes and expressive speech synthesis. It is for engineers, developers, or managers who evaluate speech technologies or integrate them into practical applications